Dynamic single-cell transcriptomic reveals the cellular heterogeneity and a novel fibroblast subpopulation in laryngotracheal stenosis - Ziwei Liao; Yangyang Zheng; Mingjun Zhang; Xiaoyan Li; Jing Wang; Hongming Xu (Biology Direct)
Abstract Background Laryngotracheal stenosis (LTS), a pathological narrowing of the upper airway caused by excessive extracellular matrix (ECM) deposition, often leads to dyspnea and even respiratory failure. However, systematic studies addressing the specific subpopulations and their contribution to LTS development still remain underexplored. Results We collected laryngotracheal tissue at multiple time points of LTS rat model, established by injuring their laryngotracheal lining, and performed dynamic single-cell RNA sequencing (scRNA-seq) to elucidate the transcriptomic atlas of LTS development. The results showed, from the inflammatory state to the repair/fibrotic state, infiltration of immune cells such as monocyte macrophages decreased and fibroblast increased. We delineated the markers and functional status of different fibroblasts subsets and identified that fibrotic fibroblasts may originate from multiple fibroblast subpopulations, including a new subpopulation characterized by the expression of chondrogenic markers such as Ucma and Col2a1, we designated this subcluster as chondrocyte injury-related fibroblasts (CIRF). Furthermore, we categorized monocytes/macrophages into several subtypes and identified that SPP1 high macrophages represented the largest macrophage subpopulation in LTS, providing evidence to clarify the importance of SPP1 macrophages in fibrosis disease. Our findings also revealed the interactions among these cells to explore the molecular mechanism associated with LTS pathogenesis. Conclusions Our study, for the first time, conducted dynamic scRNA-seq on LTS, revealing the cellular heterogeneity and providing a valuable resource for exploring the intricate molecular landscape of LTS. We propose CIRF may represent a tissue-specific fibroblast lineage in LTS and potentially originate from cells in the perichondrium of the trachea and transform into fibrotic fibroblasts. Integration of our study with those of other respiratory fibrotic diseases will allow for a comprehensive understanding of airway remodeling in respiratory diseases and exploring potential new therapeutic targets for their treatment.